The Role of NF-κB Triggered Inflammation in Cerebral Ischemia - Jover-Mengual, Teresa; Hwang, Jee-Yeon; Byun, Hyae-Ran; Court-Vazquez, Brenda L.; Centeno, José M.; Burguete, María C.; Zukin, R. Suzanne (Frontiers in Cellular Neuroscience, 2021)
Cerebral ischemia is a devastating disease that affects many people worldwide every year. The neurodegenerative damage as a consequence of oxygen and energy deprivation, to date, has no known effective treatment. The ischemic insult is followed by an inflammatory response that involves a complex interaction between inflammatory cells and molecules which play a role in the progression towards cell death. However, there is presently a matter of controversy over whether inflammation could either be involved in brain damage or be a necessary part of brain repair. The inflammatory response is triggered by inflammasomes, key multiprotein complexes that promote secretion of pro-inflammatory cytokines. An early event in post-ischemic brain tissue is the release of certain molecules and reactive oxygen species (ROS) from injured neurons which induce the expression of the nuclear factor-kappaB (NF-κB), a transcription factor involved in the activation of the inflammasome. There are conflicting observations related to the role of NF-κB. While some observe that NF-κB plays a damaging role, others suggest it to be neuroprotective in the context of cerebral ischemia, indicating the need for additional investigation. Here we discuss the dual role of the major inflammatory signaling pathways and provide a review of the latest research aiming to clarify the relationship between NF-κB mediated inflammation and neuronal death in cerebral ischemia.